Building Refactoring Tools: Insights from RefactorEx - Pereira, Gabriel Philippe; Vegi, Lucas Francisco da Matta; Di Iorio, Vladimir (Anais do Workshop em Engenharia de Software para Programação Funcional (SE4FP), 2025)
Refactoring plays a crucial role in software maintenance and evolution, yet emerging programming languages often lack the tooling to automatically and confidently perform the refactoring tasks. This paper presents insights gained from developing RefactorEx, a refactoring tool for the Elixir functional language. We discuss architectural considerations, design patterns and technical challenges encountered while implementing automated code transformations. The presented patterns and lessons aim to provide some guidance for researchers and developers seeking to build similar tooling.